PENYULUHAN TENTANG PENGGUNAAN INSTRUMEN AKREDITASI SATUAN PENDIDIKAN (IASP) UNTUK KEPALA SEKOLAH MENENGAH KEJURUAN (SMK) DI KOTA DEPOK - Muhammad Yusro (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2022)
Abstract Improving the quality of education through accreditation activities is a government commitment that is implemented through various laws and regulations related to the national education system. School/Madrasah Accreditation activities are expected to be a driving force and can create a conducive atmosphere for the development of education and provide direction in carrying out sustainable school/madrasah quality assurance, in order to achieve the expected quality. For the community, the results of accreditation are expected to provide information about the quality of education services provided by each school/madrasah. The current condition is that many schools/madrasas do not understand the importance of accreditation, plus minimal knowledge regarding the use of the 2020 Education Unit Accreditation Instrument (IASP2020). This is due to the lack of socialization of accreditation by local governments (provincial/city education offices) due to budget and human resource limitations. This counseling activity is intended to provide socialization about the importance of school/madrasah accreditation and the use of IASP2020 in the Vocational High School (SMK) environment in Depok City. This activity was carried out in September 2022 at SMKN 2 Depok which was attended by 25 Heads of Public and Private Vocational Schools throughout the City of Depok. The activity participants were very enthusiastic about participating in counseling/directing activities related to accreditation and received additional knowledge/insight regarding the importance of accreditation and the use of IASP2020 at the SMK level. Participants hope that the next activity can involve the SMK accreditation team accompanied by practical training in completing the School/Madrasah Accreditation Assessment System (SISPENA S/M). Abstrak Peningkatan mutu pendidikan melalui kegiatan akreditasi merupakan komitmen pemerintah yang diterapkan melalui berbagai peraturan perundangan terkait sistem pendidikan nasional. Kegiatan Akreditasi Sekolah/Madrasah diharapkan menjadi pendorong dan dapat menciptakan suasana kondusif bagi perkembangan pendidikan serta memberikan arahan dalam melakukan penjaminan mutu sekolah/madrasah yang berkelanjutan, guna mencapai mutu yang diharapkan. Bagi masyarakat, hasil akreditasi diharapkan menjadi informasi tentang kualitas layanan pendidikan yang diberikan oleh setiap sekolah/madrasah. Kondisi saat ini, banyak sekolah/madrasah yang belum memahami pentingnya akreditasi, ditambah pengetahuan yang minim terkait penggunaan Instrumen Akreditasi Satuan Pendidikan tahun 2020 (IASP2020). Hal tersebut disebabkan kurangnya sosialisasi akreditasi oleh pemerintah daerah (dinas pendidikan provinsi/kota) karena keterbatasan anggaran dan SDM. Kegiatan penyuluhan ini dimaksudkan untuk memberikan sosialisasi tentang pentingnya akreditasi sekolah/madrasah serta penggunaan IASP2020 di lingkungan Sekolah Menengah Kejuruan (SMK) di Kota Depok. Kegiatan ini dilaksanakan pada bulan September 2022 bertempat di SMKN 2 Depok yang dihadiri oleh 25 Kepala SMK Negeri dan Swasta se-Kota Depok. Peserta kegiatan sangat antusias mengikuti kegiatan penyuluhan/pengarahan terkait akreditasi dan mendapat tambahan pengetahuan/wawasan terkait pentingnya akreditasi dan penggunaan IASP2020 jenjang SMK. Peserta berharap bahwa kegiatan selanjutnya dapat melibatkan tim akreditasi SMK disertai dengan latihan praktik pengisian Sistem Penilaian Akreditasi Sekolah/Madrasah (SISPENA S/M).